2022
DOI: 10.3389/fonc.2022.829041
|View full text |Cite
|
Sign up to set email alerts
|

Predicting HER2 Status in Breast Cancer on Ultrasound Images Using Deep Learning Method

Abstract: PurposeThe expression of human epidermal growth factor receptor 2 (HER2) in breast cancer is critical in the treatment with targeted therapy. A 3-block-DenseNet-based deep learning model was developed to predict the expression of HER2 in breast cancer by ultrasound images.MethodsThe data from 144 breast cancer patients with preoperative ultrasound images and clinical information were retrospectively collected from the Shandong Province Tumor Hospital. An end-to-end 3-block-DenseNet deep learning classifier was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Hence, compared with the study by Wu et al, a major highlight in our study was the larger sample size and diversity of tumor types, which might increase the universality of the nomogram model. We obtained a higher AUC value compared to the aforementioned studies with regards to prediction of HER2 status by using radiomics and a machine-learning algorithm [ 29 , 37 ]. The most probable explanation for this is that we adopted seven machine learning classifiers to develop seven prediction models and selected the one with the highest AUC value.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hence, compared with the study by Wu et al, a major highlight in our study was the larger sample size and diversity of tumor types, which might increase the universality of the nomogram model. We obtained a higher AUC value compared to the aforementioned studies with regards to prediction of HER2 status by using radiomics and a machine-learning algorithm [ 29 , 37 ]. The most probable explanation for this is that we adopted seven machine learning classifiers to develop seven prediction models and selected the one with the highest AUC value.…”
Section: Discussionmentioning
confidence: 96%
“…Generally, one feature selection method is adopted in conventional radiomics analysis. In the study by Xu et al [ 37 ], six features based on ultrasound radiomics were selected by the recursive feature elimination, and a random forest model including 90 trees was built for prediction of HER2 status, with the AUC of 0.780 and 0.740 in the training and validation sets. In order to reduce overfitting effectively, we used the ICC and Mann–Whitney U test for feature selection in the first step and LASSO regression in the second step, and we achieved better predictive performance with the LR classifier than the study by Xu et al, with AUC values of 0.804 and 0.786 in the training and validation sets, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers attempted to develop a PET-CT radiomics mechanistic learning model to predict HER2 expression status, however, the results showed that PET-CT was not sufficient to accurately predict HER2 expression status with an AUC of 0.72-0.76 (39). Xu ZL et al developed a deep learning model to predict HER2 expression in breast cancer from ultrasound images (28). In common with this study, our results also showed a lower overall diagnostic performance for HER2 status assessment using clinical parameters alone, with an AUC of 0.55-0.69.…”
Section: Discussionmentioning
confidence: 99%
“…Convolutional neural networks have had tremendous success in bioinformatics since 2012 thanks to the development of deep learning, particularly in medical imaging ( 27 ). A recent study shows that DLR can be used to analyze US images for prediction of HER2 expression status ( 28 ). However, DLR usually faces the problem of small sample learning, and this study had only 36 patients in the validation set and 108 patients in the training set.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, scientists worldwide have created a range of automated techniques for classifying HER2 status from IHC and H&E-stains. MRI and ultrasound images were also used in a study to classify HER2 status [ 13 , 14 ]. A Support Vector Machine (SVM) was used there as the approach to identify the HER2 status in MRI images.…”
Section: Related Workmentioning
confidence: 99%